PENGARUH STRES KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA KANTOR CABANG PT POS INDONESIA TANGERANG SELATAN - Muhammad Wildan; Iskandar Zulkarnain (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the extent to which Job Stress and Motivation influence employee performance at PT Pos Indonesia Tangerang Selatan. The type of research used is quantitative with a sampling technique using a saturated sampling method, so that the entire population was used as a research sample of 87 respondents. Data collection techniques were carried out through distributing questionnaires with a Likert scale, then processed using the SPSS version 25 application. Data analysis includes validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis tests. The results showed that Job Stress had a significant effect on employee performance with a simple regression equation Y = 32,263 + 0.193 X1₁. The correlation value (R) of 0.232 is classified as low, with a contribution of 5.4%. Hypothesis testing proves that tₕhitung 0.030 <0.05 and tₕhitung = 2.201 > tₜabel = 1.988, so that H₀ is rejected and H₁ is accepted. Motivation also has a significant effect on performance with the equation Y = 21.657 + 0.455 X2 The correlation value (R) of 0.492 indicates a low relationship, with a contribution of 24.2%. Hypothesis testing shows tₕhitung 0.000 <0.05 and t count = 5.206 > ttable 1.988, so H₀ is rejected and H₁ is accepted. Simultaneously, Motivation and Work Discipline on Employee Performance have a positive effect with the multiple regression equation Y = 18.366 + 0.11X1 + 0.429 X2. The correlation coefficient value (R) of 0.508 indicates a moderate category with a contribution of 25.9% while the remaining 74.1% is influenced by other factors outside this study. In addition, the F test results show a calculated F of 14.644 > F table 3.11 with a significance value of 0.000 < 0.05, so H₃ is accepted.